Development of laboratory tests to predict the lubricity properties of diesel fuels and their application to the development of highly refined diesel fuels - Bovington,C; Caprotti,R; Meyer,K; Spikes,HA (Tribotest, 1995)
In the last few years there has been an increasing requirement for the provision of environmentally benign diesel fuels. However, the introduction of such fuels into service has been associated with high levels of field failure of rotary distribution fuel pumps due to wear. This is because the refining processes necessary to produce ecologically acceptable fuels result in greatly reduced levels of sulphur compounds, aromatics, and polar material, many of which are potential lubricity agents. This paper describes the development of bench test methods to evaluate diesel fuel lubricity and thus enable the identification of appropriate ‘solutions’. It has been found that the key to obtaining good correlation between field experience and bench tests is (1) to reproduce the thermal conditions present in operating pump contacts and (2) to ensure that the same mechanisms of wear operate in the bench test as in the pump environment. The physical and chemical processes involved in the lubrication of fuel pumps and the influence of temperature on these processes are outlined. As a result of the work described in this paper, effective additive solutions have been discovered for controlling the failure of diesel fuel pumps in the field and a provisional ISO (ISO/TC 22 / SC 7 M595: ‘Diesel engines diesel fuel performance requirement and test method for assessing fuel lubricity’) and CEC test method for assessing diesel fuel lubricity has also been developed. Copyright © 1995 John Wiley & Sons, Ltd